THE INFLUENCE OF SERVICE QUALITY, PRICE, AND BRAND IMAGE ON CUSTOMER SATISFACTION ON USE JUANG JEK IN BIREUEN CITY - Tasya Dara Fonna; Ikramuddin; Widyana Verawaty Siregar; Halida Bahri (RADJA PUBLIKA, 2024)
This research aims to find out the influence of service quality, price and brand image on customer satisfaction when using Juang Jek in Bireuen City. This research was conducted at the online transportation service Juang-Jek in the city of Bireuen. The objects of this research are people in the city of Bireuen who use Juang-Jek services as their main stay in ordering food and traveling. This research involved 108 respondents from the Bireuen City community. This research data uses primary data by distributing questionnaires via a Google Form link, then processing the data via SPSS. The data that has been collected from collecting questionnaires in qualitative form is first composed to become quantitative data. Quantitative data is determined using a Likert scale. The data analysis technique in this research uses multiple linear regression analysis and the results of the research show that Service Quality has a positive and significant effect on Customer Satisfaction, Price has a positive and significant effect on Customer Satisfaction, and Brand Image has a positive and significant effect on Customer Satisfaction.